Emendas orçamentárias individuais: efeitos eleitorais, condicionantes da execução e qualidade do gasto público - Baião, Alexandre Lima (2016)
This thesis is composed of three articles. The first one seeks to resume the discussion over the effect of pork barrel politics on vote, using more detailed data and more precise methods to verify the electoral efficacy of budget amendments. In addition, this study explored which mechanisms could convert the amendments into votes, exploring the role of local political actors, like majors and non-profit organization leaders, in the mediation of deputy-voter relations. The second article presents a study on the determinants of the budget amendments execution, focusing on three factors: a) the role of the parties that have representatives in the government ministries; b) the advantage received by the occupants of leadership positions at the Lower House; c) The influence of the fiscal rules that condition the receipt of earmarked grants by the town halls. Finally, the third article takes advantage of data about the amendments applied in health to develop a novel endeavor to assess the extent to which the amendments allocation among municipalities fulfill the local demands for fund resources.